(untitled) (Global Journal of Science Frontier Research, 2017)
The Niger Delta of Nigeria has been a very controversial and topical issue in the politics of the nation and in national discusses. In recent times, the region has been witnessing rising agitations, results of years of perceived under development of the region, exploitations of its crude oil resources without due consideration of the degrading effects on the environment and marginalisation of the aborigines. This heightened the call and demand for fiscal federalism as a panacea to these perceptions because many have wondered if the Niger Delta can survive a looming post-oil era of limited revenue, evident under development; and, an agricultural sector that has suffered significant neglect and damage over the years. With a return to the traditional agriculture, the Niger Delta many believe can still retain its pride of place in agriculture among the committee of states in Nigeria given its agricultural potentials. The study therefore focused on the prospects and potentials of the Niger Delta agricultural sector. The researchers adopted a survey plan in their study using a combination of primary and secondary data. Descriptive statistics were used in data analysis where necessary.